Complications of Reduced Intensity Conditioning HSCT for XIAP Deficiency (Alloimmune Cytopenias and HLH) Successfully Managed With Donor Lymphocyte Infusion. Issue 3 (April 2015) - Varghese, Anu S.; Lee, Helena; Bonney, Denise; Hughes, Stephen; Wynn, Robert
<x xml:space="preserve">Abstract</x> X-linked inhibitor of apoptosis protein deficiency is a rare illness and although stem cell transplant is curative, full intensity conditioning is associated with high mortality rates. We describe a child with unusual complications associated with residual host lymphocytes following reduced intensity stem cell transplant. Recipient derived, donor directed, antigranulocyte antibodies led to life-threatening and prolonged neutropenia and residual recipient lymphocytes reestablished hemophagocytic lymphohistiocytosis after withdrawal of immune suppression despite high levels of whole blood chimerism. Hemophagocytic lymphohistiocytosis was abolished following specific improvement in donor T-cell chimerism after donor lymphocyte infusions, and alloimmune cytopenias were no longer evident.